Prophylactic levofloxacin in pediatric neutropenic patients during autologous hematopoietic stem cell transplantation. (27th October 2015) - Hafez, Hanafy Ahmed; Yousif, Dalia; Abbassi, Maggie; Elborai, Yasser; Elhaddad, Alaa
Abstract: Background: Using fluoroquinolone prophylaxis in pediatric neutropenic patients is a controversial issue due to the concern about emergence of resistant strains in addition to the lack of pediatric studies. This study was performed to assess the effectiveness of levofloxacin prophylaxis in pediatric patients during autologous stem cell transplantation. Methods: This was an observational study of pediatric patients who underwent autologous stem cell transplantation, comparing patients who received levofloxacin prophylaxis to historical controls. Results: A total of 96 patients were included (46 patients in the control group and 50 patients received levofloxacin). The median duration till onset of first fever was 11 d in the control group as compared to 15 d in patients who received levofloxacin (p ≤ 0.001). The incidence of infectious complications was higher in patients without levofloxacin (4/46) than those with levofloxacin (1/50). The median duration of empirical antibiotic use was 10 d in the levofloxacin group compared with 14 d in the control group (p < 0.001). Conclusion: Levofloxacin prophylaxis delayed first spike of fever, decreased the incidence of septic complications, and shortened the duration of empiric antibiotic use, but its impact on emergence of resistant organisms should be closely monitored.